Caustic ingestion by children. - Ana Barbarita Navarro Sombert; Graciela Goire Herrera; Ariel Acosta Núñez; Ledicel Nilo Gámez Fonts; Dario Díaz Vázquez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Esophageal injuries caused by the ingestion of corrosive substances (caustic) constitute one of the more dramatics affections in childhood and a challenge for pediatric surgeons. Frequently they leave esophageal strictures hard to treat, that many times require prolonged stricture dilatation and/or replacement of the esophagus. We presented the Good Clinical Practices Guideline for Caustic ingestion in children, approved by consensus in the 2nd National Good Clinical Practices Workshop in Pediatric Surgery (Manzanillo, Cuba, September 31 - October 3, 2002).